Retrograde and anterograde signaling in the crosstalk between chloroplast and nucleus - Jan, Masood; Liu, Zhixin; Rochaix, Jean-David; Sun, Xuwu (Frontiers in Plant Science, 2022)
The chloroplast is a complex cellular organelle that not only performs photosynthesis but also synthesizes amino acids, lipids, and phytohormones. Nuclear and chloroplast genetic activity are closely coordinated through signaling chains from the nucleus to chloroplast, referred to as anterograde signaling, and from chloroplast to the nucleus, named retrograde signaling. The chloroplast can act as an environmental sensor and communicates with other cell compartments during its biogenesis and in response to stress, notably with the nucleus through retrograde signaling to regulate nuclear gene expression in response to developmental cues and stresses that affect photosynthesis and growth. Although several components involved in the generation and transmission of plastid-derived retrograde signals and in the regulation of the responsive nuclear genes have been identified, the plastid retrograde signaling network is still poorly understood. Here, we review the current knowledge on multiple plastid retrograde signaling pathways, and on potential plastid signaling molecules. We also discuss the retrograde signaling–dependent regulation of nuclear gene expression within the frame of a multilayered network of transcription factors.